2021
DOI: 10.1177/10783903211033028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Risk Factors of Falling for Psychiatric Inpatients and General Ward Inpatients Who Had Fallen

Abstract: BACKGROUND: For psychiatric patients, the issue of falling is complex. OBJECTIVE: The objective of this study was to compare the risk factors for falling in psychiatric inpatients and general ward inpatients who had fallen. METHODS: The researchers first derived official fall records for 122 psychiatric inpatients and then selected 122 psychiatric inpatients who had not fallen as well as 122 general ward patients who had fallen, matched for gender, age, and length of hospital stay at the time of the fall incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…Six studies were excluded for the reasons listed in Figure 1. Another four studies were identified from the reference list, and nine studies were included in this review (Aso & Okamura, 2019; Chang & Jen, 2021; Lu et al, 2018; Seeherunwong et al, 2022). The search strategy is presented in the PRISMA framework, shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies were excluded for the reasons listed in Figure 1. Another four studies were identified from the reference list, and nine studies were included in this review (Aso & Okamura, 2019; Chang & Jen, 2021; Lu et al, 2018; Seeherunwong et al, 2022). The search strategy is presented in the PRISMA framework, shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were conducted in the United States (Estrin et al, 2009; Lavsa et al, 2010; Tsai et al, 1998) and Taiwan (Chan et al, 2013; Chang & Jen, 2021; Lu et al, 2018), one study in China (An et al, 2009), Japan (Aso & Okamura, 2019) and Thailand (Seeherunwong et al, 2022). The duration of study timeframe ranges from 3 months (Aso & Okamura, 2019) to 5 years (Chang & Jen, 2021; Estrin et al, 2009; Lavsa et al, 2010; Seeherunwong et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations